2015
DOI: 10.1186/s40064-015-1336-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of willingness to pay for physical activity of socially vulnerable groups in community-based programs

Abstract: Willingness to pay (WTP) is used to assess individuals’ value attribution to health-related quality of life interventions. Little is known about predictors of WTP for sport and physical activity in socially vulnerable groups in community-based physical activity (CBHEPA) programs. This study addresses the questions: What is the WTP for sport and physical activity of participants in CBHEPA programs, expressed in WTPmoney and WTPtime? Which factors predict WTPmoney and WTPtime? From the literature, predictors for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 71 publications
(97 reference statements)
1
6
0
Order By: Relevance
“…The mean WTP observed were also highest for those who visit parks for physical activities $49.3 (AUD), then social reasons $39.4 (AUD) and relaxation and wellbeing $23.3 (AUD). This is consistent with previous research that has found physical activity in the park to be of greater importance in predicting WTP than socio-economic or health predictors [ 29 ]. In addition, a majority of participants indicated that they would miss the park “very much” if it was not available, and their corresponding WTP amounts were also higher at $48.3 (AUD) than those who would “occasionally” or “never” miss it.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The mean WTP observed were also highest for those who visit parks for physical activities $49.3 (AUD), then social reasons $39.4 (AUD) and relaxation and wellbeing $23.3 (AUD). This is consistent with previous research that has found physical activity in the park to be of greater importance in predicting WTP than socio-economic or health predictors [ 29 ]. In addition, a majority of participants indicated that they would miss the park “very much” if it was not available, and their corresponding WTP amounts were also higher at $48.3 (AUD) than those who would “occasionally” or “never” miss it.…”
Section: Resultssupporting
confidence: 92%
“…The explanatory variables are selected based on demographic factors found in the literature to influence WTP. Demographic factors, which could predict how WTP varies, were included in the model, such as age, gender, employment, and income [ 29 , 30 ]. We expected participants who frequented parks regularly, had children, and valued the provision of parks as highly important would exhibit higher WTP values than other respondents.…”
Section: Methodsmentioning
confidence: 99%
“…954-969), price is an important barrier in dealing with payable physical activity among students. In the group of students already engaged in paid recreation, the assumption of Herens, van Ophem, Wegemakers, and Koelen (2015) states that the more frequently a person engages in paid physical activity, the more this person is able to pay for it. With a high price for this service, the empirical data for the use of paid forms of activity outweigh the theoretical data by about 24% of the ticket price and 34% of the pass price.…”
Section: Resultsmentioning
confidence: 99%
“…The willingness to pay for physical activity is especially high among members of sports clubs and those who are more frequently active (Herens et al 2015). The greater the frequency of physical activity, the higher the price the person engaged is willing to pay for it.…”
Section: Individual Experiencementioning
confidence: 99%
“…the maximum price one is willing to pay for example for health improvements [ 30 ], is limited [ 31 ]. A Dutch study among socially vulnerable groups found WTP for participating in a PA initiative to be 9.60 euro per month on average, and 16% were not willing to pay at all for sport and PA [ 31 ]. Therefore, it is important to address the question of who should pay for care–PA initiatives.…”
Section: Introductionmentioning
confidence: 99%